Black Communists Speak on Scottsboro : a Documentary History. - Howard, Walter (Temple University Press, 2007)
Black Communists Speak on Scottsboro, an account of a neglected chapter in the story of the Scottsboro saga, gives voice to a segment of the African American community that has often been ignored or distorted: black Communists.